Use of an intravenous sclerosing foam (3% sodium tetradecyl sulfate) for treatment of orbital varix in a dog. (10th January 2017) - Saunders, Rebecca S.; Scansen, Brian A.; Jung, Stephen S.; Khabiri, Hooman; Wilkie, David A.
Abstract: A 6‐month‐old intact male Standard Dachshund was referred for evaluation of a soft tissue swelling above the right eye. Examination of the right eye revealed mild lateral deviation of the globe, normal vision, and a dorsonasal soft tissue swelling. Examination of the posterior segment was normal. Dual‐phase computed tomography angiography was consistent with an orbital varix of the angularis oculi and right dorsal external ophthalmic veins with no evidence of arterial involvement. Treatment involved fluoroscopically guided coil embolization of the venous outflow with nine platinum microcoils, followed by sclerotherapy of the varix using 1.5 mL of 3% sodium tetradecyl sulfate foam. Moderate‐to‐marked swelling was noted at the treatment site in the weeks following therapy, which gradually resolved. At final reexamination 3 months post‐therapy, complete sclerosis and resolution of the orbital varix were documented. To the authors' knowledge, this is the first reported case involving the use of a sclerotic agent for successful treatment of a venous malformation in a dog.